INTEGRASI TEORI STIGMA ERVING GOFFMAN TERHADAP KEADILAN SOSIAL BAGI “GOOD LOOKING” DAN DISKRIMINASI UNTUK “BAD LOOKING” - Ayu Arbia; Arif Sugitanata (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2024)
This study explores the phenomenon of "lookism" or appearance-based discrimination, which divides individuals into two primary groups: those regarded as attractive or "good looking" and those viewed as less attractive or "bad looking." It reveals that individuals perceived to meet the standards of being good-looking gain social and economic advantages through the "halo effect," wherein their appearance positively influences assessments of their professional and moral capabilities. In contrast, those perceived as less attractive or bad-looking encounter substantial disadvantages, including discrimination in job recruitment and promotion, as well as in social and institutional interactions. Utilizing a literature review with a qualitative research approach and an analytical framework based on Erving Goffman's Stigma Theory, this research demonstrates that physical appearance acts as a discrediting stigma, significantly impacting individuals' social identity and opportunities. The analysis emphasizes the integration of stigma into institutional structures and social practices, resulting in hidden yet systematic discrimination. Furthermore, the study explicates how the media and entertainment industries, through their portrayal of unrealistic beauty standards, reinforce societal beauty stereotypes. This influence on public perceptions heightens social pressure to conform to narrow beauty standards. From a sociological perspective, the unequal distribution of "beauty capital" creates persistent inequalities that affect not only economic opportunities but also political representation and power. This research underscores the need for social interventions and policies that reduce stigma and broaden the definition of beauty, which are crucial for dismantling power structures that perpetuate appearance-based discrimination and for fostering a more inclusive and equitable society. Through an informed and data-driven approach, this study provides essential insights into how social norms and values can be reformed to minimize "lookism" bias and enhance appreciation for human character diversity and complexity.